2015
DOI: 10.1093/jnci/djv367
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound as the Primary Screening Test for Breast Cancer: Analysis From ACRIN 6666

Abstract: Cancer detection rate with US is comparable with mammography, with a greater proportion of invasive and node-negative cancers among US detections. False positives are more common with US screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
165
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(190 citation statements)
references
References 39 publications
10
165
2
3
Order By: Relevance
“…Milestone studies showed that ultrasound (US) was not only a useful supplementary imaging tool of MG for women with dense breast or elevated risk [814], but an effective primary screening test for breast cancer both in the western world and in China [7, 15–18]. US was widely used as initial imaging test for breast detection in hospitals in China, and also designated as the primary screening tool in the standard protocol of the Two Cancers Screening Project jointly launched by the National Health and Family Planning Commission (former Ministry of Health of China) and the All-China Women's Federation [19–22].…”
Section: Introductionmentioning
confidence: 99%
“…Milestone studies showed that ultrasound (US) was not only a useful supplementary imaging tool of MG for women with dense breast or elevated risk [814], but an effective primary screening test for breast cancer both in the western world and in China [7, 15–18]. US was widely used as initial imaging test for breast detection in hospitals in China, and also designated as the primary screening tool in the standard protocol of the Two Cancers Screening Project jointly launched by the National Health and Family Planning Commission (former Ministry of Health of China) and the All-China Women's Federation [19–22].…”
Section: Introductionmentioning
confidence: 99%
“…Among 202 cancers detected in the intervention group, 144 (71.3%) were stage 0 or I compared to only 79/152 (52.0%) in the control group (p=0.019). In the ACRIN 6666 trial, supplemental ultrasound improved detection of mostly node-negative invasive breast cancers (25/32 [78%], of women diagnosed with breast cancer seen only on ultrasound had stage I disease); detection benefits of ultrasound occurred in women whose breast density was visually estimated at only 25–40% though there was a trend for greater increase in cancer detection with increasing breast density (6). …”
mentioning
confidence: 99%
“…Hand held ultrasound (HHUS) has been a mainstay of diagnostic breast imaging12. While the impact of HHUS in breast imaging is clear and it has been shown to be prominent in detection of mammographically occult breast cancers in women with dense breast parenchyma1, the use has been limited due to operator variability and reproducibility of two dimensional images3.…”
mentioning
confidence: 99%
“…While the impact of HHUS in breast imaging is clear and it has been shown to be prominent in detection of mammographically occult breast cancers in women with dense breast parenchyma1, the use has been limited due to operator variability and reproducibility of two dimensional images3. Recent developments in paradigm of ultrasound breast imaging now allow fully automated45 and true 3D image acquisition and reconstruction6.…”
mentioning
confidence: 99%